Lyophilized equine platelet-rich plasma (L-GFequina) antagonize the Reproductive toxicity and oxidative stress Induced by Cyclophosphamide in female rats - Ahmed Sabry S. Abdoon; Ahmed M.E Al-Atrash; Seham S. Soliman; Amro M. El-Sanea; Amina A. Gamal el Din; Hossam M. Fahmy (BMC, 2023)
Abstract Background The antineoplastic agent Cyclophosphamide (CP) induces reproductive toxicity. New strategies for protecting ovarian tissue damage in women with chemotherapy-induced reproductive toxicity are essential. This study was designed to evaluate the possible protective effect of combined treatment with L-GFequina on CP-induced reproductive toxicity in the mature female rat. Methodology Forty mature female rats were assigned into four groups: First group, control: rats were intraperitoneally injected (IP) with 200 µl sterile saline solution on days 1 and 10; Group 2 (CP): were IP injected with 75 mg/kg on days 1 and 10 to induce POI); Group 3 (CP + L-GFequina): as in group 2 + IP injected with 200 µl rehydrated L-GFequina half-hour after CP injection on day 1 and 10); Group 4 (L-GFequina): rats were IP injected with 200 µl L-GFequina on day 1 and 10). Blood samples were collected for a complete blood picture and determinations of nitric oxide and malondialdehyde. Animals were sacrificed on Day-21, and genitalia was dissected, weighed, and fixed in 10% formalin for histopathological and morphometric evaluation. Results On day 21 of the experiment, body weight, ovarian parameters (Ovarian weight, uterine weight, the number of ovarian follicles, and corpora lutea (CL) were determined, and histopathological changes, blood profile, as well as antioxidant activity assessment, were performed. CP significantly suppresses ovarian and uterine functions and increased MAD, NO levels, RBCs, hemoglobin, WBCs, and platelet count compared to the control group ( P < 0.05). While, in CP + L-GFequina group, gross, histomorphometry parameters, blood, and biochemical markers were similar to that in the control. IP injection of L-GFequina alone significantly (P < 0.05) increased body weight, and ovarian and uterine morphometry compared with the control. Conclusion co-administration of L-GFequina with CP might protect the reproductive organs in rats through its high antioxidant capacity.